Nilai-nilai Filosofis pada Simbol Tari Pedang Masyarakat Berkas Kota Bengkulu - Rian Hasbi Amrullah (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2023)
Abstract: The Philosophy Values of Tari Pedang Symbol Berkas Village of Bengkulu. Tari pedang is one of the dances originating from Bengkulu City. This dance art has an important place in society so that it is always used in various activities in life. Apart from being a means of entertainment that is seen in its beautiful shape, dance also functions as a means of ceremony. The main factor of dance in a ceremony, is not merely seeing its beauty, but which becomes a force in the ritual ceremony and has a meaning that can influence and help the surrounding environment as desired by the supporting community. The problem in this research is how the philosophical meaning of the Masyaralat Sword Dance in Bengkulu City filesThis study aims to find out the philosophy meaning contained in each Tari Pedang series. This study uses qualitative descriptive research method using semiotic Theory. Data collection in this study uses interview, observation and documentation techniques. Furthermore, data analysis uses data reduction, data analysis and conclusion drawing. This dance is to welcome great guests. then the core of the Tari Pedang consists of 9 movements. First, rendai movement are meaningful as expertising is needed in the life to be useful to others. Secondly, sembah rendai movements are meaningful as a tribute to the great guests and the tari pedang program. Secondly, the wrong movement of the waist is a meaningful movement as a policy in making decisions. Third, the movement of langkah tigas refer tocustum term “Adat bersendikan Syara, dan Syara bersendikan Kitabullah”. Fourth, the movement of tangan beseluk as the meaning of dancer’s skill in martial arts who are ready ake care of grear guest. Fifth, the movement of mecah langkah as a means of the dance’s valor who are ready in any case sprightly. Sixth, the movement of ari pane bertudung pedang as a meaning of violence as the final solution in an emergency as self protection. Seventh, the movement of gayung as means don’t solve the problem by a rude way. Eight, the movement of meletak pedang as means be careful by the problrm that have been completed. Nineth, the movement sembah rendai as a tribute to the great guests and to the spectators present at the tari pedang program.